The Impact of Ethical Judgment, Locus of Control, and Organizational Commitments to Whistleblowing - Andreani Hanjani; Agus Purwanto; RR Karlina Aprilia Kusumadewi (JAFFA, 2018)
This research aims at examining the influence of ethical judgment, locus of control and organizational commitment of auditor intention to whistleblowing. The population of this research was all internal auditors in Central Java Inspectorate, Semarang Regency and Semarang City. Data used in this research were primary data, which were obtained with questionnaire survey method. Analysis method used was multiple regression. The result of this research showed that ethical judgement, locus of control and organizational commitments have positive and significant influence to auditor intention in doing whistleblowing. Meanwhile, gender has no significant influence to whistleblowing. Besides, the age has significant impact toward negative to whistleblowing intensity.